Relationship between finger and wrist deformities in rheumatoid arthritis. Issue 6 (December 1983) - Read, G O; Solomon, L; Biddulph, S
Abstract : The present study was undertaken to test the hypothesis that there is a significant correlation between the position of the wrist and metacarpophalangeal angulation in the common rheumatoid hand deformities. Measurements were carried out on radiographs of the hand from 2 comparative groups: 67 patients (134 hands) with classical or definite rheumatoid arthritis (RA), and a control series of 50 adults (100 hands) attending the routine fracture clinic. Rheumatoid patients were unselected and included those with a variety of hand deformities. The results showed a statistically significant relationship between finger and wrist deformities in patients with RA but not in the normal controls.